2020
DOI: 10.1101/2020.03.02.972836
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interleukin-25-mediated resistance against intestinal trematodes does not depend on the generation of Th2 responses

Abstract: Interleukin-25 (IL-25) plays a major role in resistance against intestinal helminth infections as initiator of protective Th2 responses. However, recent studies have challenged the contribution of this cytokine in both the polarization of the response towards a Th2 phenotype and the parasite rejection. We have used the experimental model Echinostoma caproni-ICR mice to investigate the participation of this cytokine in resistance to intestinal helminths. ICR mice are characterized by their inability to respond … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Susceptibility of mice to E. caproni infection depends on the ability of the host to respond to IL-25 production (Muñoz-Antoli et al ., 2016 a ; Álvarez-Izquierdo et al ., 2020 a ). Primary infections become chronic and characterized by elevated levels of inflammation and tissue damage in relation to the lack of IL-25 production (Muñoz-Antoli et al ., 2007).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Susceptibility of mice to E. caproni infection depends on the ability of the host to respond to IL-25 production (Muñoz-Antoli et al ., 2016 a ; Álvarez-Izquierdo et al ., 2020 a ). Primary infections become chronic and characterized by elevated levels of inflammation and tissue damage in relation to the lack of IL-25 production (Muñoz-Antoli et al ., 2007).…”
Section: Discussionmentioning
confidence: 99%
“…However, mice develop partial resistance to secondary infection in relation to the innate production of IL-25 as a consequence of the curation of the primary infection (Muñoz-Antoli et al, 2016a, 2016b. Furthermore, Álvarez-Izquierdo et al (2020a) demonstrated that type gut microbiota (Zaph et al, 2008;Sawa et al, 2011;Donaldson et al, 2015;Watanabe et al, 2017). IL-25-mediated intestinal immune regulation is impaired in mice in the absence of microbiota (Sawa et al, 2011;Donaldson et al, 2015;Watanabe et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Resistance to echinostome infections has been traditionally associated with the development of Th2 responses, mainly mediated by interleukin 4 (IL-4) and/or IL-13 (Brunet et al ., 2000; Toledo and Fried, 2005; Sotillo et al ., 2011; Cortés et al ., 2017 b ; Toledo et al ., 2019). However, recent studies suggest that resistance depends on the ability of the host to maintain the mucosal homoeostasis in a process mediated by IL-25 (Muñoz-Antoli et al ., 2016; Álvarez-Izquierdo et al ., 2020 a , 2020 b ). Resistance is associated with hyperplasia of local tuft cells and production of IL-25 which operates by facilitating the maintenance of the epithelial homoeostasis that could be ultimately responsible for parasite rejection (Muñoz-Antoli et al ., 2016; Cortés et al ., 2017 b ; Álvarez-Izquierdo et al ., 2020 a , 2020 b ).…”
Section: Echinostomiasismentioning
confidence: 99%